Networked Learning in Professional Education Using Virtual Enterprises - Vescoukis, V. C.; Retalis, S.; Michiotis, S. (Proceedings of the International Conference on Networked Learning, 2000)
No doubt, the use of new technologies in education has attracted the attention of researchers and education providers for several years. Many cases have been proposed, where the use of new technological tools, especially of network-based ones, can be applied in order to favour the educational process by adding some value. New educational models have been proposed. Tools, frameworks and educational content in electronic form, have been presented and many are still under development using support from the private and public sector, as well as from the EU. Although there are several cases where networked learning has been a paradigm of great success, it cannot be said that the human and capital investments made in the area have been proven profitable" in terms of improving the quality of at least some categories of education. Perhaps it is the co-incidence of the introduction of networked learning with the restructuring of educational systems that hold the wide adaptation of new methods in education, or perhaps it is simply too early. No matter what the case is, we are still trying to identify areas where networked learning can be applied, which educational models, tools and, last but not least, types of educational software are effective.